Efeito do solutol® HS 15 na fase aguda da epileptogênese em modelo experimental de epilepsia do lobo temporal - Silva, Carmem Lúcia de Arroxelas (2019)
Epilepsy is a neurological disorder characterized by the occurrence of recurrent and spontaneous epileptic seizures (SESs) that affects approximately 50 million people worldwide. Temporal Lobe Epilepsy (TLE) is the most common type and presents a high index (40%) of refractoriness to pharmacological treatment. There is an urgent need, therefore, for the search for new drugs and therapeutic alternatives. Solutol® HS 15 (SOL) is a synthetic substance used as a drug carrier that has shown an inhibitory effect on calcium influx in neural cell culture and neuroprotective in an experimental model of cerebral ischemia. Our hypothesis is that Solutol® HS 15 has an anticonvulsive and neuroprotective action in an ELT experimental model. This study aimed to evaluate the effect of Solutol® HS 15 on Status Epilepticus (SE) and neurodegeneration present in the acute phase of epileptogenesis. For this, male Wistar rats were divided into 4 experimental groups: 1. SOL + Li-PILO group: intrahippocampal microinjection (ih) of 1uL of Solutol® HS 15 (1.6 mg / kg, n = 10) and 2. SAL + Li-PILO group: microinjection (1hL) of saline solution (0.9%, n = 7) 30 minutes before intraperitoneal (ip) injection of pilocarpine (30mg / kg). The action of pilocarpine was potentiated by administration (i.p.) of lithium chloride (127 mg / kg) 16 hours prior to administration of pilocarpine; 3. SOL group: microinjection (i.h) of Solutol® HS 15 (1.6 mg / kg, n = 5) and 4. SHAM group (n = 5). For the analyzes of the crisis profile, the animals were video monitored during latency and 90 minutes of SE. The evaluation of neurodegeneration was done by Fluoro-Jade histochemistry 24 hours after SE. Histochemistry analyzes were directed to sub-regions of hippocampal formation (Horn of Ammon: CA1 and CA3; and Hilo). Statistical analyzes were performed using Student t test (GraphPad, Prism 6.0). The animals in the SOL + Li-PILO group had a significant decrease in the number of seizures during SE (38%) compared to the SAL + LiPILO group (62%) (p = 0.010) and a significant decrease in the amount of (FJ +) neurons in the CA3 region of the ipsilateral (ips.) and contralateral (con.) hippocampus (SOL + Li-PILO: ips 27% and with 32%; SAL + Li-PILO: ips. 68%) (ips p = 0.026 and con. p = 0.010). The animals of the SOL and SHAM Group. did not present JF + neurons. Solutol® HS 15 has an inhibitory effect on seizures during SE and hippocampal neurodegeneration present in the acute phase of epileptogenesis in an ELT experimental model. The data are promising to investigate the potential of Solutol® HS 15 for anticonvulsive role in animals with CREs.